A qualitative exploration of park-based physical activity in adults with serious mental illness: Insights from peers and peer counselors. (October 2022) - Besenyi, G.M.; Bramwell, R.C.; Heinrich, K.M.; Mailey, E.L.; McEvoy, J.P.; Davis, C.L.
Abstract: Statement of the problem: Park-based physical activity (PA) is associated with positive health outcomes (social support, energy, self-esteem, mood, less depression). Integrating park-based PA into peer-led mental health services is an innovative approach that can address health disparities in persons with serious mental illness (SMI). Yet, to date, few PA interventions capitalize on peer counselor (PC) capacity, and none have focused on park-based PA. The purpose of this qualitative study was to ascertain the perspectives of adults with SMI and their counselors about park-based PA to inform the development of a park-based PA intervention lead by PCs. Methods: In Spring/Summer 2018, we conducted six 1-h focus groups (FGs) with adults with SMI, and four 1-h FGs with PCs and social workers. Using the person-based approach framework, open-ended questions elicited information regarding peer PA behavior and park use, PA participation motives/barriers, and preference for park-based PA. PCs discussed knowledge and promotion of PA in peer group settings, willingness to lead PA activities, and feedback on intervention strategies. Results: Peer FGs averaged 49 ± 8 min. Peer data were coded into three overarching themes: current PA, motivators, and barriers. Peer counselor FGs averaged 60 ± 5 min. Data were coded into five themes: current peer group PA, barriers to peer group PA, motivators for peer group PA, PA intervention recommendations, and implementation barriers. Conclusion: Peers and PCs were interested in participating/leading in outdoor PA. Social support, motivation, PA self-efficacy, health concerns, weather, transportation, and PC training are important considerations for intervention development. Highlights: Few peers were knowledgeable about PA guidelines. Peer counselors consider PA promotion part of their role, but lack training. Outdoor PA preferred among peers and peer counselors. Peer-led park-based PA is a feasible and scalable strategy for adults with SMI. Key park-based intervention considerations include social support, transportation, health concerns and weather.